SAGA: results of a second trial testing a mentalizing-based reading intervention on children and staff in early childhood education - Linnavalli, Tanja; Martikainen, Silja; Belfrage, Filippa; Kalland, Mirjam (Frontiers in Education, 2024)
Social–emotional development is a key factor in child well-being and development, and studying how it can be supported in early childhood is crucial. This study acted as a second trial testing the efficacy of a shared story book reading intervention combined with mentalizing discussions (SAGA), on children’s (N = 196) social–emotional development. In contrast to the first trial, the current trial utilized a group comprised of mostly multilingual children, attending daycare in a minority language. In addition, we investigated the effect of the intervention on the mentalizing capacity of the staff. The staff of the early childhood education and care (ECEC) centers were trained to lead discussions about story characters’ mental states with children three times a week. The staff’s mentalization ability was measured by the self-reported Mentalization Scale (MentS). Children’s social–emotional development was evaluated via the teacher-reported Strengths and Difficulties Questionnaire SDQ, and verbal fluency via a subtest from the NEPSY II neuropsychological test battery. After 12 weeks, the children in the SAGA group showed improvement in prosocial behavior, whereas no change was observed in the control group. Furthermore, within the SAGA group, the children showing initially lower scores for prosocial behavior displayed larger improvement compared to their peers with higher scores at baseline. No such intervention-based improvement emerged in verbal fluency. Unlike in the first trial, the intervention did not have an impact on children’s internalizing or externalizing problems. The results suggest that story reading sessions combined with mentalizing discussions about emotions, thoughts, and intentions of the story characters may support children’s social–emotional development within the realm of prosocial behavior, although the possibility to decrease children’s internalizing and externalizing problems with these sessions remains unclear based on the two trials. In addition, training the ECEC staff in mentalization theory and guiding them toward mind-related dialogs improved staff motivation to mentalize, as well as their child-related mentalization capacity.